Analysis on Influence of the Dispersion Degree of PVA Fibers on Pavement Performance of Cement-Stabilized Macadam. (13th October 2019) - Yuan, Lingqing; Liang, Naixing; Zhao, Chunhua
Abstract : In order to study the effect of PVA fiber dispersion on the performance of cement-stabilized macadam as pavement base material, the dispersion factor F vc is introduced ( F vc = 1 − C vc, C vc refers to dispersion coefficient of relative mass fraction proportion coefficient) as a factor to judge the dispersion degrees. Besides, the connections among F vc and the compressive strength of the splitting strength of cement-stabilized macadam in various curing periods are analyzed. The research conclusions reveal that (1) when the mass ratio of PVA fibers to coal ash is higher than 1 : 50, resulting F vc > 0.95, it means the PVA fibers can disperse evenly in the cement-stabilized macadam; (2) both the compressive strength and the cleavage strength of cement-stabilized macadam with PVA fibers are proportional to F vc ; moreover, both the compressive strength and the splitting strength of cement-stabilized macadam with PVA fibers are obviously stronger than those in the common macadam; and (3) under the same curing period and with the same F vc value, both the compressive strength and the splitting strength in the first type of cement-stabilized macadam (volume content: 0.9 kg/m 3 of PVA fibers) are stronger than those in the second type of cement-stabilized macadam (volume content: 0.6 kg/m 3 of PVA fibers).